Evaluation of intravoxel incoherent motion fitting methods in low‐perfused tissue. Issue 5 (22nd August 2016) - Meeus, Emma M.; Novak, Jan; Withey, Stephanie B.; Zarinabad, Niloufar; Dehghani, Hamid; Peet, Andrew C.
Abstract : Purpose: To investigate the robustness of constrained and simultaneous intravoxel incoherent motion (IVIM) fitting methods and the estimated IVIM parameters ( D, D* and f ) for applications in brain and low‐perfused tissues. Materials and Methods: Model data simulations relevant to brain and low‐perfused tumor tissues were computed to assess the accuracy, relative bias, and reproducibility (CV%) of the fitting methods in estimating the IVIM parameters. The simulations were performed at a series of signal‐to‐noise ratio (SNR) levels to assess the influence of noise on the fitting. Results: The estimated IVIM parameters from model simulations were found significantly different ( P  < 0.05) using simultaneous and constrained fitting methods at low SNR. Higher accuracy and reproducibility were achieved with the constrained fitting method. Using this method, the mean error (%) for the estimated IVIM parameters at a clinically relevant SNR = 40 were D 0.35, D * 41.0 and f 4.55 for the tumor model and D 1.87, D * 2.48, and f 7.49 for the gray matter model. The most robust parameters were the IVIM‐ D and IVIM‐ f . The IVIM‐ D * was increasingly overestimated at low perfusion. Conclusion: A constrained IVIM fitting method provides more accurate and reproducible IVIM parameters in low‐perfused tissue compared with simultaneous fitting. Level of Evidence : 3 J. MAGN. RESON. IMAGING 2017;45:1325–1334